EFEKTIVITAS FILM PENDEK CERDIK TERHADAP PENGETAHUAN PENGENDALIAN HIPERTENSI PADA LANSIA PESERTA POSBINDU (Politeknik Kesehatan Kemenkes Bandung, 2021)
The prevalence of elderly with hypertension in Indonesia covers 63% of the 63 million cases of them. The high incidence of hypertension has encouraged the birth of risk factor control to prevent complications through behavior modification as CERDIK programs. Although the CERDIK program has been continuously socialized, it cannot be denied that the percentage of implementing CERDIK behavior is still relatively low. Therefore, the researcher designed an alternative health promotion media in the form of a short film to provide knowledge to the elderly about CERDIK life behavior. The purpose of this study was to determine the difference in knowledge scores before and after respondents given the CERDIK short film intervention. This study used a pre-experimental study with a one-group pretest-posttest design on 34 elderly participants in 2nd Hamlet Posbindu, Cimahi Urban Village, Central Cimahi Health Center in 2021. This study used a questionnaire measuring instrument. Data analysis used univariate and bivariate with Wilcoxon signed rank test at 0.05. The results of data analysis showed that the use of health promotion media